(untitled) (Singaporean Journal of Business Economics and Management, 2013)
The Purpose of this study is investigating the relationship between manager’s business intelligence and the performance of food industry companies in Rasht industrial city. This paper is a descriptive - analytical research and a correlational one, and in aspect of applied target is based on structural equation. Statistical universe of this research include all food industry companies in Rasht industrial city, which are 32 companies, and sample size through Krejcie and Morgan Table includes 30 companies which are selected by simple random sampling method. A researcher made questionnaire, special to managers, has been used to data collection. The content validity of the questionnaire has been confirmed by experts and scholars, and its reliability calculated respectively0.937, 0.871 by Cronbach’s alpha coefficient for two variables of business intelligence and performance. Business intelligence questionnaire in this research is researcher made, and according to dimensions of business intelligence includes 42 questions, and performance includes 11 questions. Collected data has analyzed by SPSS software; research findings indicate that business intelligence has positive and significant impact on the performance. Thus, organizational learning has the strongest relationship with the performance of company, and policies of continuous improvement are the second strong one.